2018
DOI: 10.3748/wjg.v24.i23.2441
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of using marginal liver grafts in living donor liver transplantation

Abstract: Liver transplantation (LT) is one of the most effective treatments for end-stage liver disease caused by related risk factors when liver resection is contraindicated. Additionally, despite the decrease in the prevalence of hepatitis B virus (HBV) over the past two decades, the absolute number of HBsAg-positive people has increased, leading to an increase in HBV-related liver cirrhosis and hepatocellular carcinoma. Consequently, a large demand exists for LT. While the wait time for patients on the donor list is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 128 publications
0
14
0
Order By: Relevance
“…In addition, with the global development of surgical procedures, perioperative management, and immunosuppression regimens, accompanied by the establishment and updating of guidelines, pediatric LT has evolved rapidly, including in China. As we recently found that donor liver quality affects the post‐LT prognosis, 25 this quality is now controlled strictly, and the number of DDLTs performed has declined slightly. We now use both methods to mitigate the problems of organ shortage and save more children's lives.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, with the global development of surgical procedures, perioperative management, and immunosuppression regimens, accompanied by the establishment and updating of guidelines, pediatric LT has evolved rapidly, including in China. As we recently found that donor liver quality affects the post‐LT prognosis, 25 this quality is now controlled strictly, and the number of DDLTs performed has declined slightly. We now use both methods to mitigate the problems of organ shortage and save more children's lives.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, with the global development of surgical procedures, perioperative management, and immunosuppression regimens, accompanied by the establishment and updating of guide-lines, pediatric LT has evolved rapidly, including in China. As we recently found that donor liver quality affects the post-LT prognosis,25…”
mentioning
confidence: 95%
“…Graft to recipient size mismatch was defined according to graft weight in relation to body weight of the recipient (graft-recipient ratio). Graft weight of less than 2% of patient body weight was defined as "small for size", graft size of more than 4% of patient body weight was defined as "large for size" [24] [25].…”
Section: Sirs and Sepsis Were Defined According To The International Pediatric Sepsismentioning
confidence: 99%
“…Hepatic IR injury also increases the risks of post‐LT tumor recurrence and metastasis by activating hypoxia and angiogenesis signaling pathways for tumor cell growth, migration, and invasion 6,7 . On the other hand, due to the shortage of liver donors, using marginal liver grafts, including fatty liver (steatosis less than 30%) in LT is feasible and acceptable in selected patients 8,9 . However, donor steatosis increases the risk of postoperative morbidity and mortality 10‐12 .…”
Section: Introductionmentioning
confidence: 99%